2019
DOI: 10.1371/journal.pone.0216830
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Leptospira spp. in rats as early spatial predictor for human disease in an endemic urban area

Abstract: Background Leptospirosis is considered a neglected zoonosis associated with infrastructure problems and low socioeconomic status, particularly slums. Since the disease is mainly transmitted in urban settings by rat urine, this risk factor may be important predictor tool for prompt control and effective prevention at the local level in urban endemic areas. Accordingly, the present study aimed to propose an early spatial predictor tool for human leptospirosis in urban settings, to test the methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
(56 reference statements)
0
20
0
1
Order By: Relevance
“…These results can help public health authorities to assess spatial variations in the risk related to the presence of rats in the city. Because rats are ubiquitous in urban settings, have a small home range (Feng and Himsworth 2014), and because monitoring Leptospira infection in hosts is achievable on carcasses that can be provided by pest management professionals (Strand et al 2015), brown rats can be used as early spatial predictors of human leptospirosis cases in cities (Pellizzaro et al 2019) but also as sentinels for the early detection of emerging pathogenic Leptospira in urban ecosystems. The implementation of a surveillance programme through a One Health approach that monitors the Leptospira status of the wildlife reservoir, surveys the bacterial load in the environment, and identifies the circulating Leptospira species using an automated workflow is of high interest to urban health.…”
Section: Resultsmentioning
confidence: 99%
“…These results can help public health authorities to assess spatial variations in the risk related to the presence of rats in the city. Because rats are ubiquitous in urban settings, have a small home range (Feng and Himsworth 2014), and because monitoring Leptospira infection in hosts is achievable on carcasses that can be provided by pest management professionals (Strand et al 2015), brown rats can be used as early spatial predictors of human leptospirosis cases in cities (Pellizzaro et al 2019) but also as sentinels for the early detection of emerging pathogenic Leptospira in urban ecosystems. The implementation of a surveillance programme through a One Health approach that monitors the Leptospira status of the wildlife reservoir, surveys the bacterial load in the environment, and identifies the circulating Leptospira species using an automated workflow is of high interest to urban health.…”
Section: Resultsmentioning
confidence: 99%
“…The southern regions of China have many major rivers and lakes, and abundant water energy resources. This area also contains a large number of ponds and small lakes, which are often contaminated by animal carriers that excrete pathogenic leptospires (Zhang, Wang, et al, ; Zhao et al, ). Previous reports showed that the leptospirosis has been considered as a neglected zoonosis associated with infrastructure problems and low socioeconomic status, particularly in slums and rural areas (Morikawa et al, ; Pellizzaro et al, ). Farmers engaged in rice cultivation, field management and animal herding are highly vulnerable to contracting leptospirosis (Suárez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in illicit slaughter the animal stays in an open place, under environmental temperature, with the presence of other animals such as carnivorous birds and dogs ( Figure 2 ) that lick the carcass during the slaughter or feed on the remains of the carcass ( 23 ) and can be infected if the slaughtered animal is sick. The contact of the blood of a sick animal with open wounds or mucous membranes of the slaughterers who perform the slaughter also propitiate the spread of zoonosis, particularly the ones considered as neglected zoonosis associated with infrastructure problems and low socioeconomic status ( 32 ).…”
Section: Environment Riskmentioning
confidence: 99%